Through murky waters: conservation implications from evaluating the drivers of diversity and abundance on coral reef communities in Cambodia - Fiona Chong; Morokot Long; Stéphane De Palmas; Sorn Srenh; Stefanie M. Rog; Matthew Glue; Ouk Vibol; James Davis Reimer (Biodiversity and Conservation, 2026)
Cambodia’s coral reefs are vital for supporting marine biodiversity and coastal livelihoods, but they remain understudied and are increasingly threatened by overfishing, habitat degradation, and climate change. Using Reef Check citizen science data from 91 reef sites (2021–2023), we examined how turbidity and productivity, sea surface temperature (SST), hard coral cover and marine protected area (MPA) designation shape coral reef communities across nearshore and offshore reefs. Our analyses revealed distinct benthic, fish, and invertebrate communities nearshore and offshore. Offshore reefs, characterized by lower turbidity and dominated by branching corals, hosted more fusiliers (Caesionidae) and wrasses (Labridae), and had higher abundances of fish and invertebrates. Nearshore turbid reefs dominated by massive and encrusting corals exhibited higher invertebrate diversity despite lower fish and invertebrate abundance. Hard coral cover increased fish abundance and biomass. Warmer SSTs were associated with reduced fish diversity. Reefs within the Koh Rong Marine National Park did not have higher fish or invertebrate diversity, abundance or targeted fish biomass than outside the MPA, which may reflect mixed zoning, site selection history and enforcement limitation. Our findings showcase the contemporary status of Cambodian reefs, and the potential of citizen science to support baseline monitoring. We recommend expanding MPAs to connect offshore and nearshore reefs while accounting for fishing pressure and enforcement capacity. We also show that integrating satellite data with citizen monitoring can aid adaptive marine conservation planning.

Federated learning: global insights from local plant data - Mirza Shoaib; Priyanka Reddy; Guodong Long; Matthew J. Hayden; Surya Kant (Trends in Plant Science, 2026)

Vegetation preference and the puzzle of abandonment: high-quality spawning habitat remains unused by Pacific herring (Clupea pallasii) - Jacob T. Dingwall; Jessica Qualley; Matthew Thompson; Sydni Long; Amanda E. Bates (Marine Environmental Research, 2026)

Huron Chipper a Broadly Adapted Chip-Processing Variety with Long-Term Storage Potential and Resistance to Late Blight and Common Scab - David S. Douches; Joseph J. Coombs; William L. Behling; Gregory E. Steere; Matthew L. Zuehlke; Christopher M. Long (American Journal of Potato Research, 2026)
Huron Chipper is a high yielding round white chip-processing variety with resistance to late blight ( Phytophthora infestans ) and tolerance to common scab ( Streptomyces scabies ). Selected from a cross between the Michigan State University breeding lines MSQ070-1 and MSR156-7, it was designated MSW485-2 during its initial evaluation and development. Huron Chipper is high yielding and broadly adapted, showing equal or better agronomic performance compared to Snowden in all major growing regions in the United States. In on-farm trials in Michigan and national SNAC trials, Huron Chipper had higher total and marketable yields and specific gravity (1.083 in Michigan, 1.088 on average nationally) compared to Snowden. Formally released in 2018, Huron Chipper offers producers an agronomically competitive alternative to Snowden and Atlantic with better resistance to common scab, late blight, and blackspot bruise with high chip-processing quality up to eight months post-harvest.

Lynch syndrome integrative epidemiology and genetics (LINEAGE): rationale for cohort design - Swati G. Patel; Holli A. Loomans-Kropp; Zachariah H. Foda; Bryson W. Katona; Suzi Birz; Carol A. Burke; Jordan Clawson; Brian Furner; Camille Hochheimer; Elizabeth Magnan; Luigi Ricciardiello; Harminder Singh; et al. (Familial Cancer, 2026)

Review on mercury transformations and trophic transfer in upland forest ecosystems - Ganxing Liu; Matthew Long-Hei Cheng; Runnan Lyu; Martin Tsz-Ki Tsui (Chemosphere, 2026)

Correction to: Socio‑economic position and healthy ageing across the life course: a systematic review of longitudinal studies - Yisheng Ye; Chengxu Long; Kia‑Chong Chua; Darío Moreno‑Agostino; Matthew Prina (GeroScience, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Ecology of community reassembly: Movements and diets of megafauna during a decade of restoration in Mozambique - Matthew C. Hutchinson; Reena H. Walker; Joel O. Abraham; Justine A. Becker; Dominique D. Gonçalves; Ciara M. Nutter; Johan Pansu; Erin M. Phillips; Arjun B. Potter; Beto Soares Tenente; Marc E. Stalmans; Ryan A. Long; et al. (Ecology, 2026)
The last decade has brought a worldwide surge of interest in rewilding—the repopulation of large herbivores and carnivores—as a strategy for conserving species and reviving ecosystem functions. Rewilding initiatives, if closely monitored, can provide unique insights into the ecology of the world's largest animals at otherwise impossible spatial and temporal scales. Capitalizing on these opportunities, and developing a knowledge base to guide future restoration efforts, requires the collection and dissemination of long‐term data that document community reassembly. To date, such data are virtually nonexistent: most megafaunal restoration projects are nascent and/or have not been rigorously monitored. Since 2008, the Gorongosa Restoration Project, in Mozambique's Gorongosa National Park, has facilitated the recovery of megafauna populations that were severely depleted or extirpated during the country's civil war (1977–1992). For over a decade, we have monitored Gorongosa's large‐herbivore populations to understand how animal behavior and trophic interactions change as communities reassemble. Here, we present spatiotemporally explicit data sets on the movements and diets of large herbivores in Gorongosa between 2013 and 2025, along with annual rainfall data. This period encompassed extremes of climate (including some of the driest and wettest years on record) and the reintroduction, starting in 2018, of locally extinct apex predators and scavengers: African wild dog ( Lycaon pictus ), leopard ( Panthera pardus ), spotted hyena ( Crocuta crocuta ), and side‐striped jackal ( Lupulella adusta ). We used GPS telemetry to monitor 277 herbivores of seven species (listed below with number of individuals collared, median duration of tracking, and median number of locations per individual): Cape bushbuck ( Tragelaphus sylvaticus : 103 individuals; 280 days; 6646 fixes), nyala ( T. angasii : 37 individuals; 306 days; 6789 fixes), greater kudu ( T. strepsiceros : 80 individuals; 300 days; 17,365 fixes), common eland ( T. oryx : 10 individuals; 334 days; 15,783 fixes), waterbuck ( Kobus ellipsiprymnus : 22 individuals; 13 days; 2877 fixes), plains zebra ( Equus quagga : 7 individuals; 212 days; 1171 fixes), and African savanna elephant ( Loxodonta africana : 18 individuals; 706 days; 33,122 fixes). For 295 individuals that were immobilized during this work, we present morphological measurements (chest girth, body length, hind‐foot length, weight), reproductive status and nutritional condition (ultrasound measurements, palpation scores), and fate (mortality date and cause, if known). For diet analysis, we used DNA metabarcoding to identify and quantify the relative abundances of plant taxa in 3785 fecal samples from 27 mammal species belonging to 11 families and 7 orders. In all, we recorded 516 food‐plant taxa from at least 87 plant families and 39 orders. For Gorongosa's 15 most common large herbivores, the median sampling depth was 216 fecal samples per species (interquartile range 156–279); the overall median sampling depth was 92 samples per species (range 1–499). We include basic metadata collected in the field (e.g., date, time, GPS location, animal sex, and age) along with laboratory notes and information on plant taxonomic identification. These data are valuable not just as a window on one ecosystem's recovery from armed conflict, but also as a resource for macroecology, meta‐analysis, and synthetic studies of animal movement, diet, and the dynamics of community reassembly. The data are freely available for use and this paper should be cited whenever data are reused; see Data : Metadata : Class III.B.4 for additional details.

Socio-economic position and healthy ageing across the life course: a systematic review of longitudinal studies - Yisheng Ye; Chengxu Long; Kia-Chong Chua; Darío Moreno-Agostino; Matthew Prina (GeroScience, 2026)
Increasing health inequalities among older adults globally illustrate the urgent need for effective interventions. Socio-economic position (SEP), which reflects an individual's social and economic standing, may affect healthy ageing through various life course mechanisms. However, longitudinal associations between life course SEP and healthy ageing as a multidimensional construct remain unclear. We conducted a comprehensive systematic review of longitudinal studies investigating the associations between life course SEP indicators (including education, income, occupation, wealth) and multidimensional healthy ageing outcomes. A systematic literature search was conducted across four databases (MEDLINE, Embase, PsycINFO, and Web of Science) from inception to April 2025. Due to the heterogeneity in the operationalisation of SEP and healthy ageing, a narrative synthesis was performed (Prospero CRD42023418728). 47 articles were included in the review. Across multiple SEP indicators and life stages, higher educational levels (39/43 studies) and higher income/wealth (31/36 studies) were positively associated with better healthy ageing outcomes. Occupation showed inconsistent evidence. Life-course evidence showed childhood SEP disadvantage predicted poorer later-life outcomes (13/17 studies), with cumulative multi-stage disadvantage showing additive effects (5 studies) and upward mobility conferring benefits (3 studies). These patterns manifested in three age-related inequality trajectories: widening (18/23 studies), convergence, and persistence, with education-cognitive disparities showing strongest widening effects. Cross-national evidence revealed regional specificities. Studies also identified sex/gender moderation effects (5 studies) and examined mediating pathways (6 studies). Higher education showed the most consistent protective effects, while income/wealth effects were complex. Health inequalities widened with age, highlighting lasting childhood impacts. Targeted interventions addressing early educational investment and life stage-specific strategies are needed for reducing healthy ageing inequalities.

CORRIGENDUM, Long Term Exposure to Benzo[b]fluoranthene Does Not Induce Mutations in MutaMouse Male Germ Cells. Reprod Toxicol, 2025, 137:108985 http://doi.org/10.1016/j.reprotox.2025.108985 - Madison T. Stewart; Gu Zhou; Danielle P.M. LeBlanc; Annette E. Dodge; Matthew J. Meier; Andrew Williams; Alexandra S. Long; Paul A. White; Carole L. Yauk; Francesco Marchetti (Reproductive Toxicology, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Blackberry, an Attractive Deep Purple Potato Variety with Resistance to Common Scab and Extreme Resistance to Potato Virus Y - David S. Douches; Joseph J. Coombs; William L. Behling; Gregory E. Steere; Matthew L. Zuehlke; Tomás D. Lopes; Joseph I. Ulasi; Christopher M. Long (American Journal of Potato Research, 2025)
Blackberry is a tablestock variety with uniquely deep purple skin and flesh. The tubers have an attractive, uniform, round shape with common scab resistance and low incidence of internal defects. It also carries the Rysto marker for extreme resistance to potato virus Y. When baked or microwaved, the tuber flesh is a brilliant deep purple with an enjoyable mild taste. It was selected in 2011 from a cross between two breeding lines COMN07-W112BG1 and MSU200-5PP. Although primarily oriented towards the fresh market, Blackberry is an all-purpose variety that also has the ability to chip out of the field. Yields are high under irrigated conditions and specific gravity averaged 1.068 in on-farm trials in Michigan.

Manistee, a new Round-White Early to Mid-Season Maturing Potato Variety with Excellent Long-Term Storage Potential - David S. Douches; Joseph J. Coombs; William L. Behling; Ray Hammerschmidt; Greg E. Steere; Matthew L. Zuehlke; Christopher M. Long (American Journal of Potato Research, 2025)
Manistee is a round white chip-processing potato ( Solanum tuberosum ) variety developed for long-term storage. Evaluated as MSL292-A, Manistee is a selection from a cross between Snowden and the chip-processing breeding line MSH098-2. The tubers of Manistee are compressed, round with shallow eyes and early to mid-season maturity. Field testing and on-farm trials show that this variety has high yield potential with specific gravity comparable to Snowden and similar to better tolerance to blackspot bruise. Manistee was formally released in 2013 and has demonstrated reliable and excellent long-term storage chip-processing quality up to eight months post-harvest which extends the chip-processing storage season beyond Snowden. Furthermore, preliminary studies with Manistee, Snowden, Lamoka and Pike tuber disks demonstrated that Manistee started the wound healing process faster than Lamoka and Pike and slightly faster than Snowden which supports observations of stable and reliable commercial storage of the tubers for chip-processing.

Petoskey A High Gravity Chip-Processing Variety with Long-term Storage Potential and Resistance to Common Scab - David S. Douches; Joseph J. Coombs; William L. Behling; Gregory E. Steere; Matthew L. Zuehlke; Christopher M. Long (American Journal of Potato Research, 2025)
Petoskey is a high specific gravity round white chip-processing potato variety with resistance to common scab ( Streptomyces scabies ). It was selected from a cross between Beacon Chipper and the breeding line MSG227-2, and designated MSV030-4 during the trialling phase of its development. This variety has high yield potential with attractive round, uniform tubers with netted skin. Five years of field testing in Michigan demonstrate that yield of Petoskey is similar to Snowden with higher specific gravity averaging 1.089. Out-of-the field chip scores were comparable to Snowden while Petoskey chip scores outperform Snowden in long-term storage trials at eight months post-harvest. Petoskey has a medium upright canopy and a mid to full season maturity with excellent long-term storage chip-processing quality. This variety has performed well in Michigan in on-farm trials and multistate national SNAC trials. Formally released in 2019, Petoskey is a comparable alternative to Snowden with strong resistance to common scab. Producers can expect higher specific gravity and longer storage potential than Snowden with high chip-processing quality up to eight months post-harvest.

Mackinaw: A Round White Potato Variety with Excellent Long-Term Storage Chip-Processing Quality and Resistance To Late Blight, Potato Virus Y, Golden Cyst Nematode and Tolerance To Common Scab - David S. Douches; Joseph J. Coombs; William L. Behling; Gregory E. Steere; Matthew L. Zuehlke; Jaime Willbur; Christopher M. Long (American Journal of Potato Research, 2025)
Mackinaw is a disease resistant round white chip-processing potato with resistance to potato virus Y (PVY), late blight ( Phytophthora infestans ), and tolerance to common scab ( Streptomyces scabies ). Mackinaw also carries the TG689 marker for the H1 resistance gene to golden cyst nematode ( Globodera rostochiensis ) race Ro1. Designated as MSX540-4 during the trialling phase of its development, it was selected from a cross between the cultivars Saginaw Chipper and Lamoka. Field testing in Michigan show that this variety has average yield potential, similar to Snowden, with high specific gravity averaging 1.087. Mackinaw has a strong vine with a mid- to late-season maturity, producing a large percentage of A-sized tubers with a low incidence of internal defects and excellent long-term storage chip-processing quality. Mackinaw performed well in on-farm trials in Michigan and in multistate SNAC trials showing broad adaptation, especially in the northern tier states. Formally released in 2017, Mackinaw offers a unparalleled combination of disease resistance, long-term storage potential, and excellent chip-processing quality out of the field and out of long-term storage.

Long term exposure to benzo[b]fluoranthene does not induce mutations in Mutamouse male germ cells - Madison T. Stewart; Gu Zhou; Danielle P.M. LeBlanc; Annette E. Dodge; Matthew J. Meier; Andrew Williams; Alexandra S. Long; Paul A. White; Carole L. Yauk; Francesco Marchetti (Reproductive Toxicology, 2025)

Identification of SfABCC2 as the critical receptor for Cry1Fa and Cry1Ab in Spodoptera frugiperda via CRISPR-mediated gene knockouts - Zheng Zhang; Shuwen Wu; Ying Long; Wei Huang; Matthew Bramlett; Yihua Yang; Yidong Wu (Pesticide Biochemistry and Physiology, 2025)

Estimating park visitation in Canadian national parks using volunteered geographic information (VGI) - Matthew Ketchin; Jed A. Long (Journal of Outdoor Recreation and Tourism, 2025)

Causes of Differences in the Tropical Pacific SST Warming Pattern Projected by CMIP6 Models - Jun Ying; Matthew Collins; Robin Chadwick; Shangfeng Chen; Xiaoming Hu; Tao Lian; Shangmin Long (Advances in Atmospheric Sciences, 2025)
The inter-model difference in the tropical Pacific SST warming pattern is a big stumbling block for reliable projections of global climate change. Here by conducting an inter-model Empirical Orthogonal Function (EOF) analysis as well as an ocean mixed-layer heat budget, we find that the first two modes of inter-model difference in the SST warming pattern projected by 30 CMIP6 models, explaining more than three-quarters of the total inter-model variance, are both tied to different cloud–radiation feedbacks. The EOF1 mode that captures the different magnitudes of El Niño-like warming as well as the largest inter-model variance in the far eastern equatorial Pacific, is likely driven by highly diverse cloud–radiation feedbacks in the east and, to a lesser extent, by differing changes in the oceanic vertical temperature gradient. The EOF2 mode that mainly represents the different magnitudes of SST warming in the western equatorial Pacific, is associated with differing levels of negative cloud–radiation feedback over the central equatorial Pacific through a dynamic air–sea coupled process involving both the Bjerknes feedback and the wind–evaporation–SST feedback. Considering in isolation the robust common model bias of a weak negative cloud–radiation feedback over the central equatorial Pacific, the projected SST warming in the western equatorial Pacific is likely to be smaller than the multi-model ensemble mean, thereby presenting a more weakeened zonal SST gradient than expected, implying the potential for more severe climate extremes under global warming.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Hypogene sulfide precipitation during phyllic alteration: insights from copper isotopic evolution of the Dexing porphyry Cu–Mo–Au deposit, South China - Jia-Feng He; Guo-Guang Wang; Matthew J. Brzozowski; Pei Ni; Xiang-Long Luo; Jun Mu; Weiqiang Li (Mineralium Deposita, 2025)

Review of mercury pollution research in Southeast Asian marine environments - Martin Tsz-Ki Tsui; Shaoyi Wang; Matthew Long-Hei Cheng (Marine Pollution Bulletin, 2025)

Exploring species and functional diversity of fishes in Cambodian coastal habitats using eDNA metabarcoding - Charlotte G. Clay; Fabian Gösser; Matthew Glue; Morokot Long; Stefanie M. Rog; Pablo Sinovas; James D. Reimer (Coral Reefs, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

From nutrients to fish: Impacts of mesoscale processes in a global CESM-FEISTY eddying ocean model framework - Kristen M. Krumhardt; Matthew C. Long; Colleen M. Petrik; Michael Levy; Frederic S. Castruccio; Keith Lindsay; Lev Romashkov; Anna-Lena Deppenmeier; Rémy Denéchère; Zhuomin Chen; Laura Landrum; Gokhan Danabasoglu; et al. (Progress in Oceanography, 2024)

Strain and kinematics within the Salmon River suture zone and western Idaho shear zone, Idaho, USA: Exploring the contribution of ductile stretching to mass transfer and exhumation in fold-thrust and transpressional systems - Andrea E. Richardson; Sean P. Long; William K. Barba; Matthew P. McKay (Journal of Structural Geology, 2024)

Understanding the extreme differentiation of granitic magmas through elemental geochemistry and Fe isotope signatures - Xiang-Long Luo; Chang-Zhi Wu; Jia-Xin She; Matthew J. Brzozowski; De-Hong Du; Shichao An; Weiqiang Li (Geochimica et Cosmochimica Acta, 2024)

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Bioaccumulation of pollutants in the green-lipped mussel Perna viridis: Assessing pollution abatement in Victoria Harbour and its adjacent aquaculture area, Hong Kong, and the minimal human health risks from mussel consumption - Ryan Kar-Long Leung; Apple Pui Yi Chui; Xiaoshou Liu; Hang-Wai Lee; Matthew Ming-Lok Leung; Youji Wang; Menghong Hu; Kevin Wing Hin Kwok; Rudolf Shiu Sun Wu; Ling Jin; Hang-Kin Kong; James Kar-Hei Fang (Marine Pollution Bulletin, 2024)

Improved capabilities of global ocean reanalyses for analysing sea level variability near the Atlantic and Gulf of Mexico Coastal U.S. - Xue Feng; Matthew J. Widlansky; Magdalena A. Balmaseda; Hao Zuo; Claire M. Spillman; Grant Smith; Xiaoyu Long; Philip Thompson; Arun Kumar; Gregory Dusek; William Sweet (Frontiers in Marine Science, 2024)
Realistic representation of monthly sea level anomalies in coastal regions has been a challenge for global ocean reanalyses. This is especially the case in coastal regions where sea levels are influenced by western boundary currents such as near the U.S. Atlantic Coast and the Gulf of Mexico. For these regions, most ocean reanalyses compare poorly to observations. Problems in reanalyses include errors in data assimilation and horizontal resolutions that are too coarse to simulate energetic currents like the Gulf Stream and Loop Current System. However, model capabilities are advancing with improved data assimilation and higher resolution. Here, we show that some current-generation ocean reanalyses produce monthly sea level anomalies with improved skill when compared to satellite altimetry observations of sea surface heights. Using tide gauge observations for coastal verification, we find the highest skill associated with the GLORYS12 and HYCOM ocean reanalyses. Both systems assimilate altimetry observations and have eddy-resolving horizontal resolutions (1/12°). We found less skill in three other ocean reanalyses (ACCESS-S2, ORAS5, and ORAP6) with coarser, though still eddy-permitting, resolutions (1/4°). The operational reanalysis from ECMWF (ORAS5) and their pilot reanalysis (ORAP6) provide an interesting comparison because the latter assimilates altimetry globally and with more weight, as well as assimilating ocean observations over continental shelves. We find these attributes associated with improved skill near many tide gauges. We also assessed an older reanalysis (CFSR), which has the lowest skill likely due to its lower resolution (1/2°) and lack of altimetry assimilation. ACCESS-S2 likewise does not assimilate altimetry, although its skill is much better than CFSR and only somewhat lower than ORAS5. Since coastal flooding is influenced by sea level anomalies, the recent development of skilful ocean reanalyses on monthly timescales may be useful for better understanding the physical processes associated with flood risks.

Insights into progress of wheat breeding in arid and infertile areas of China in the last 14 years - Long Li; Jingyi Wang; Chaonan Li; Xinguo Mao; Xiaoqing Zhang; Junwei Sun; Ke Zhang; Yuping Liu; Matthew P. Reynolds; Ziguang Yang; Ruilian Jing (Field Crops Research, 2024)

Deoxygenation, Acidification and Warming in Waquoit Bay, USA, and a Shift to Pelagic Dominance - Matthew H. Long; Jordan W. Mora (Estuaries and Coasts, 2023)
Coastal nutrient pollution, or eutrophication, is commonly linked to anthropogenic influences in terrestrial watersheds, where land-use changes often degrade water quality over time. Due to gradual changes, the management and monitoring of estuarine systems often lag environmental degradation. One example can be found at the Waquoit Bay National Estuarine Research Reserve, where we developed an analysis framework to standardize and analyze long-term trends in water quality and submerged vegetation data from monitoring programs that began in the 1990s. These programs started after the nearly complete loss of historically extensive Zostera marina (eelgrass) meadows throughout the estuary. Recently, eelgrass only persisted in small, undeveloped sub-embayments of the estuary, with conservative declines of over 97% in areal coverage. Over the past 2 decades, the average deoxygenation, acidification, and warming were −24.7 µmol O 2 kg −1 (−11%), 0.006 µmol H + kg −1 (+ 34%), and 1.0 °C (+ 4%), respectively. Along with the loss of eelgrass, there was also a decline in macroalgal biomass over 3 decades, resulting in a system dominated by pelagic metabolism, indicated by a 71% increase in water column chlorophyll a concentrations since 2009. This recent increase in phytoplankton biomass, which is highly mobile and transported throughout the estuary by tides, has resulted in recent degradation of isolated embayments despite their lower nutrient loads. This shift toward pelagic dominance in Waquoit Bay may indicate that other eutrophic and warming estuaries may also shift toward pelagic dominance in the future, as the Northeastern US is one of the fastest warming regions across the world.

Extensive regional variation in the phenology of insects and their response to temperature across N orth A merica - Peter O. Dunn; Insiyaa Ahmed; Elise Armstrong; Natasha Barlow; Malcolm A. Barnard; Marc Bélisle; Thomas J. Benson; Lisha L. Berzins; Chloe K. Boynton; T. Anders Brown; Melissa Cady; Kyle Cameron; et al. (Ecology, 2023)
Climate change models often assume similar responses to temperatures across the range of a species, but local adaptation or phenotypic plasticity can lead plants and animals to respond differently to temperature in different parts of their range. To date, there have been few tests of this assumption at the scale of continents, so it is unclear if this is a large‐scale problem. Here, we examined the assumption that insect taxa show similar responses to temperature at 96 sites in grassy habitats across North America. We sampled insects with Malaise traps during 2019–2021 ( N = 1041 samples) and examined the biomass of insects in relation to temperature and time of season. Our samples mostly contained Diptera (33%), Lepidoptera (19%), Hymenoptera (18%), and Coleoptera (10%). We found strong regional differences in the phenology of insects and their response to temperature, even within the same taxonomic group, habitat type, and time of season. For example, the biomass of nematoceran flies increased across the season in the central part of the continent, but it only showed a small increase in the Northeast and a seasonal decline in the Southeast and West. At a smaller scale, insect biomass at different traps operating on the same days was correlated up to ~75 km apart. Large‐scale geographic and phenological variation in insect biomass and abundance has not been studied well, and it is a major source of controversy in previous analyses of insect declines that have aggregated studies from different locations and time periods. Our study illustrates that large‐scale predictions about changes in insect populations, and their causes, will need to incorporate regional and taxonomic differences in the response to temperature.

Adverse impacts of high-density microplastics on juvenile growth and behaviour of the endangered tri-spine horseshoe crab Tachypleus tridentatus - James Kar-Hei Fang; Tsz Wan Tse; Elizaldy Acebu Maboloc; Ryan Kar-Long Leung; Matthew Ming-Lok Leung; Max Wang-Tang Wong; Apple Pui-Yi Chui; Youji Wang; Menghong Hu; Kit Yue Kwan; Siu Gin Cheung (Marine Pollution Bulletin, 2023)

Soil antibiotic resistance genes accumulate at different rates over four decades of manure application - Yuting Zhang; Xiying Hao; Ben W. Thomas; Tim A. McAllister; Matthew Workentine; Long Jin; Xiaojun Shi; Trevor W. Alexander (Journal of Hazardous Materials, 2023)

Mechanisms of individual variation in large herbivore diets: Roles of spatial heterogeneity and state‐dependent foraging - Reena H. Walker; Matthew C. Hutchinson; Arjun B. Potter; Justine A. Becker; Ryan A. Long; Robert M. Pringle (Ecology, 2023)
Many populations of consumers consist of relatively specialized individuals that eat only a subset of the foods consumed by the population at large. Although the ecological significance of individual‐level diet variation is recognized, such variation is difficult to document, and its underlying mechanisms are poorly understood. Optimal foraging theory provides a useful framework for predicting how individuals might select different diets, positing that animals balance the “opportunity cost” of stopping to eat an available food item against the cost of searching for something more nutritious; diet composition should be contingent on the distribution of food, and individual foragers should be more selective when they have greater energy reserves to invest in searching for high‐quality foods. We tested these predicted mechanisms of individual niche differentiation by quantifying environmental (resource heterogeneity) and organismal (nutritional condition) determinants of diet in a widespread browsing antelope (bushbuck, Tragelaphus sylvaticus ) in an African floodplain‐savanna ecosystem. We quantified individuals' realized dietary niches (taxonomic richness and composition) using DNA metabarcoding of fecal samples collected repeatedly from 15 GPS‐collared animals (range 6–14 samples per individual, median 12). Bushbuck diets were structured by spatial heterogeneity and constrained by individual condition. We observed significant individual‐level partitioning of food plants by bushbuck both within and between two adjacent habitat types (floodplain and woodland). Individuals with home ranges that were closer together and/or had similar vegetation structure (measured using LiDAR) ate more similar diets, supporting the prediction that heterogeneous resource distribution promotes individual differentiation. Individuals in good nutritional condition had significantly narrower diets (fewer plant taxa), searched their home ranges more intensively (intensity‐of‐use index), and had higher‐quality diets (percent digestible protein) than those in poor condition, supporting the prediction that animals with greater endogenous reserves have narrower realized niches because they can invest more time in searching for nutritious foods. Our results support predictions from optimal foraging theory about the energetic basis of individual‐level dietary variation and provide a potentially generalizable framework for understanding how individuals' realized niche width is governed by animal behavior and physiology in heterogeneous landscapes.

Climate drivers of Southern Ocean phytoplankton community composition and potential impacts on higher trophic levels - Kristen M. Krumhardt; Matthew C. Long; Zephyr T. Sylvester; Colleen M. Petrik (Frontiers in Marine Science, 2022)
Southern Ocean phytoplankton production supports rich Antarctic marine ecosystems comprising copepods, krill, fish, seals, penguins, and whales. Anthropogenic climate change, however, is likely to drive rearrangements in phytoplankton community composition with potential ramifications for the whole ecosystem. In general, phytoplankton communities dominated by large phytoplankton, i.e., diatoms, yield shorter, more efficient food chains than ecosystems supported by small phytoplankton. Guided by a large ensemble of Earth system model simulations run under a high emission scenario (RCP8.5), we present hypotheses for how anthropogenic climate change may drive shifts in phytoplankton community structure in two regions of the Southern Ocean: the Antarctic Circumpolar Current (ACC) region and the sea ice zone (SIZ). Though both Southern Ocean regions experience warmer ocean temperatures and increased advective iron flux under 21st century climate warming, the model simulates a proliferation of diatoms at the expense of small phytoplankton in the ACC, while the opposite patterns are evident in the SIZ. The primary drivers of simulated diatom increases in the ACC region include warming, increased iron supply, and reduced light from increased cloudiness. In contrast, simulated reductions in ice cover yield greater light penetration in the SIZ, generating a phenological advance in the bloom accompanied by a shift to more small phytoplankton that effectively consume available iron; the result is an overall increase in net primary production, but a decreasing proportion of diatoms. Changes of this nature may promote more efficient trophic energy transfer via copepods or krill in the ACC region, while ecosystem transfer efficiency in the SIZ may decline as small phytoplankton grow in dominance, possibly impacting marine food webs sustaining Antarctic marine predators. Despite the simplistic ecosystem representation in our model, our results point to a potential shift in the relative success of contrasting phytoplankton ecological strategies in different regions of the Southern Ocean, with ramifications for higher trophic levels.

Haplotype variants of Sr46 in Aegilops tauschii, the diploid D genome progenitor of wheat - Naveenkumar Athiyannan; Yunming Long; Houyang Kang; Sutha Chandramohan; Dhara Bhatt; Qijun Zhang; Daryl L. Klindworth; Matthew N. Rouse; Timothy L. Friesen; Robert McIntosh; Peng Zhang; Kerrie Forrest; et al. (Theoretical and Applied Genetics, 2022)

FDA Approaches in Monitoring Drug Quality, Forces Impacting the Drug Quality, and Recent Alternative Strategies to Assess Quality in the US Drug Supply - Philip J. Almeter; James T. Isaacs; Aaron N. Hunter; Bradley S. Henderson; Thomas Platt; Billie J. Mitchell; David Do; Alyssa B. Brainard; Joshua E. Brown; Rachael M. Stone; Bao-Han Nguyen; Matthew F. Warren; et al. (Journal of Pharmaceutical Innovation, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Detecting climate signals in populations across life histories - Stéphanie Jenouvrier; Matthew C. Long; Christophe F. D. Coste; Marika Holland; Marlène Gamelon; Nigel G. Yoccoz; Bernt‐Erik Sæther (Global Change Biology, 2022)
Climate impacts are not always easily discerned in wild populations as detecting climate change signals in populations is challenged by stochastic noise associated with natural climate variability, variability in biotic and abiotic processes, and observation error in demographic rates. Detection of the impact of climate change on populations requires making a formal distinction between signals in the population associated with long‐term climate trends from those generated by stochastic noise. The time of emergence (ToE) identifies when the signal of anthropogenic climate change can be quantitatively distinguished from natural climate variability. This concept has been applied extensively in the climate sciences, but has not been explored in the context of population dynamics. Here, we outline an approach to detecting climate‐driven signals in populations based on an assessment of when climate change drives population dynamics beyond the envelope characteristic of stochastic variations in an unperturbed state. Specifically, we present a theoretical assessment of the time of emergence of climate‐driven signals in population dynamics ( ). We identify the dependence of on the magnitude of both trends and variability in climate and also explore the effect of intrinsic demographic controls on . We demonstrate that different life histories (fast species vs. slow species), demographic processes (survival, reproduction), and the relationships between climate and demographic rates yield population dynamics that filter climate trends and variability differently. We illustrate empirically how to detect the point in time when anthropogenic signals in populations emerge from stochastic noise for a species threatened by climate change: the emperor penguin. Finally, we propose six testable hypotheses and a road map for future research.

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Diversity and Disease: The Effects of Coral Diversity on Prevalence and Impacts of Stony Coral Tissue Loss Disease in Saint Thomas, U.S. Virgin Islands - Sophia V. Costa; Stephanie J. Hibberts; Danielle A. Olive; Kayla A. Budd; Alexys E. Long; Sonora S. Meiling; Madyson B. Miller; Kelsey M. Vaughn; Claudia I. Carrión; Maksym B. Cohen; Annie E. Savage; Matthew F. Souza; et al. (Frontiers in Marine Science, 2021)
Stony coral tissue loss disease (SCTLD) was first observed in St. Thomas, U.S. Virgin Islands (USVI) in January 2019. This disease affects at least 20 scleractinian coral species; however, it is not well understood how reef diversity affects its spread or its impacts on reef ecosystems. With a large number of susceptible species, SCTLD may not follow the diversity-disease hypothesis, which proposes that high species diversity is negatively correlated with disease prevalence. Instead, SCTLD may have a higher prevalence and a greater impact on reefs with higher coral diversity. To test this, in 2020 we resampled 54 sites around St. Thomas previously surveyed in 2017 or 2019 by the National Oceanic and Atmospheric Administration National Coral Reef Monitoring Program. These sites represented a variety of species diversity values [categorized into poor (<12 spp. rich.) and rich (≥12 spp. rich.)] in multiple disease zones (Endemic: disease present ≥ 9 months; Epidemic: disease present 2–6 months; Control and Emergent: disease present no disease/<2 months). We hypothesized that, contrary to the diversity-disease hypothesis, sites with high species diversity (as measured by species richness or Simpson’s index) would have higher disease prevalence within the epidemic zone, and that high species diversity sites would have a greater impact from disease within the endemic zone. Results indicated a significant positive relationship between disease prevalence and diversity in the epidemic zone, and a similar trend in the endemic zones. Additionally, a negative relationship was seen between pre-outbreak diversity and loss of diversity and coral cover within the endemic zone. This supports the hypothesis that higher diversity predicts greater disease impact and suggests that SCTLD does not follow the diversity-disease hypothesis. Within the epidemic zone, the species with the highest SCTLD prevalence were Dendrogyra cylindrus , Colpophyllia natans , and Meandrina meandrites , while in the endemic zone, Diploria labyrinthiformis , Pseudodiploria strigosa , Montastraea cavernosa , and Siderastrea siderea had the highest SCTLD prevalence. Understanding the relationship between species diversity and SCTLD will help managers predict the most vulnerable reefs, which should be prioritized within the USVI and greater Caribbean region.

Detecting Climate Signals in Southern Ocean Krill Growth Habitat - Zephyr T. Sylvester; Matthew C. Long; Cassandra M. Brooks (Frontiers in Marine Science, 2021)
Climate change is rapidly altering the habitat of Antarctic krill ( Euphausia superba ), a key species of the Southern Ocean food web. Krill are a critical element of Southern Ocean ecosystems as well as biogeochemical cycles, while also supporting an international commercial fishery. In addition to trends forced by global-scale, human-driven warming, the Southern Ocean is highly dynamic, displaying large fluctuations in surface climate on interannual to decadal timescales. The dual roles of forced climate change and natural variability affecting Antarctic krill habitat, and therefore productivity, complicate interplay of observed trends and contribute to uncertainty in future projections. We use the Community Earth System Model Large Ensemble (CESM-LE) coupled with an empirically derived model of krill growth to detect and attribute trends associated with “forced,” human-driven climate change, distinguishing these from variability arising naturally. The forced trend in krill growth is characterized by a poleward contraction of optimal conditions and an overall reduction in Southern Ocean krill habitat. However, the amplitude of natural climate variability is relatively large, such that the forced trend cannot be formally distinguished from natural variability at local scales over much of the Southern Ocean by 2100. Our results illustrate how natural variability is an important driver of regional krill growth trends and can mask the forced trend until late in the 21st century. Given the ecological and commercial global importance of krill, this research helps inform current and future Southern Ocean krill management in the context of climate variability and change.

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Assessing the Skill of a High-Resolution Marine Biophysical Model Using Geostatistical Analysis of Mesoscale Ocean Chlorophyll Variability From Field Observations and Remote Sensing - Rachel Eveleth; David M. Glover; Matthew C. Long; Ivan D. Lima; Alison P. Chase; Scott C. Doney (Frontiers in Marine Science, 2021)
High-resolution ocean biophysical models are now routinely being conducted at basin and global-scale, opening opportunities to deepen our understanding of the mechanistic coupling of physical and biological processes at the mesoscale. Prior to using these models to test scientific questions, we need to assess their skill. While progress has been made in validating the mean field, little work has been done to evaluate skill of the simulated mesoscale variability. Here we use geostatistical 2-D variograms to quantify the magnitude and spatial scale of chlorophyll a patchiness in a 1/10th-degree eddy-resolving coupled Community Earth System Model simulation. We compare results from satellite remote sensing and ship underway observations in the North Atlantic Ocean, where there is a large seasonal phytoplankton bloom. The coefficients of variation, i.e., the arithmetic standard deviation divided by the mean, from the two observational data sets are approximately invariant across a large range of mean chlorophyll a values from oligotrophic and winter to subpolar bloom conditions. This relationship between the chlorophyll a mesoscale variability and the mean field appears to reflect an emergent property of marine biophysics, and the high-resolution simulation does poorly in capturing this skill metric, with the model underestimating observed variability under low chlorophyll a conditions such as in the subtropics.

Resting fMRI-guided TMS results in subcortical and brain network modulation indexed by interleaved TMS/fMRI - Desmond J. Oathes; Jared P. Zimmerman; Romain Duprat; Seda S. Japp; Morgan Scully; Benjamin M. Rosenberg; Matthew W. Flounders; Hannah Long; Joseph A. Deluisi; Mark Elliott; Gavriella Shandler; Russell T. Shinohara; et al. (Experimental Brain Research, 2021)

Taxon‐specific primary production rates on coral reefs in the Florida Keys - Daniel P. Owen; Matthew H. Long; William K. Fitt; Brian M. Hopkinson (Limnology and Oceanography, 2021)
Coral reefs are known to have extremely high rates of primary production. However, common geochemical methods for determining bulk rates of reef metabolism cannot distinguish which organisms are responsible for primary production. Here we used a “bottom‐up” approach to estimate the contribution of diverse primary producers including hard corals, octocorals, and algae to gross primary production on coral reefs by scaling up taxon‐specific rates by the abundance of those taxa in the environment. Chamber‐based production rates of the dominant primary producers were obtained as a function of irradiance, the primary short‐term driver of photosynthesis. These rates were then combined with annotated three‐dimensional (3D) reconstructions of reef sections and a simple light field model to estimate reef‐scale gross and net primary production rates over time. At a degraded reef in the Florida Keys octocorals and algae were the main producers, but at a more intact site a scleractinian coral ( Acropora palmata ) was the most important producer. As a validation of the approach, rates of primary production estimated using the “bottom‐up” approach were compared with in situ eddy covariance fluxes. The daily integrated rates agreed within 16%, though maximal production was ~ 35% lower in the “bottom‐up” approach likely due to under‐representation of octocorals and macroalgae in the 3D reconstructions. The “bottom up” approach yielded results that were largely consistent with the in situ measurements of primary production and irradiance with the significant benefit of providing taxon‐specific and spatially‐explicit primary production rates.

On the control of subantarctic stratification by the ocean circulation - R. Justin Small; Alice K. DuVivier; Daniel B. Whitt; Matthew C. Long; Ian Grooms; William G. Large (Climate Dynamics, 2021)

Tracking Improvement in Simulated Marine Biogeochemistry Between CMIP5 and CMIP6 - Roland Séférian; Sarah Berthet; Andrew Yool; Julien Palmiéri; Laurent Bopp; Alessandro Tagliabue; Lester Kwiatkowski; Olivier Aumont; James Christian; John Dunne; Marion Gehlen; Tatiana Ilyina; et al. (Current Climate Change Reports, 2020)
Purpose of Review The changes or updates in ocean biogeochemistry component have been mapped between CMIP5 and CMIP6 model versions, and an assessment made of how far these have led to improvements in the simulated mean state of marine biogeochemical models within the current generation of Earth system models (ESMs). Recent Findings The representation of marine biogeochemistry has progressed within the current generation of Earth system models. However, it remains difficult to identify which model updates are responsible for a given improvement. In addition, the full potential of marine biogeochemistry in terms of Earth system interactions and climate feedback remains poorly examined in the current generation of Earth system models. Summary Increasing availability of ocean biogeochemical data, as well as an improved understanding of the underlying processes, allows advances in the marine biogeochemical components of the current generation of ESMs. The present study scrutinizes the extent to which marine biogeochemistry components of ESMs have progressed between the 5th and the 6th phases of the Coupled Model Intercomparison Project (CMIP).

Corrigendum: Phytoplankton Phenology in the North Atlantic: Insights From Profiling Float Measurements - Bo Yang; Emmanuel S. Boss; Nils Haëntjens; Matthew C. Long; Michael J. Behrenfeld; Rachel Eveleth; Scott C. Doney (Frontiers in Marine Science, 2020)

Racial/Ethnic Differences in Comprehension of Biospecimen Collection: a Nationwide University of Rochester Cancer Center NCI Community Oncology Research Program Study - Matthew Asare; Charles E. Heckler; Eva Culakova; Charles S. Kamen; Amber S. Kleckner; Lori M. Minasian; David S. Wendler; Michelle Feige; Carol J. Weil; Joan Long; Sharon K. Cole; Adedayo A. Onitilo; et al. (Journal of Cancer Education, 2020)

Phytoplankton Phenology in the North Atlantic: Insights From Profiling Float Measurements - Bo Yang; Emmanuel S. Boss; Nils Haëntjens; Matthew C. Long; Michael J. Behrenfeld; Rachel Eveleth; Scott C. Doney (Frontiers in Marine Science, 2020)

Ebullition of oxygen from seagrasses under supersaturated conditions - Matthew H. Long; Kevin Sutherland; Scott D. Wankel; David J. Burdige; Richard C. Zimmerman (Limnology and Oceanography, 2020)
Gas ebullition from aquatic systems to the atmosphere represents a potentially important fraction of primary production that goes unquantified by measurements of dissolved gas concentrations. Although gas ebullition from photosynthetic surfaces has often been observed, it is rarely quantified. The resulting underestimation of photosynthetic activity may significantly bias the determination of ecosystem trophic status and estimated rates of biogeochemical cycling from in situ measures of dissolved oxygen. Here, we quantified gas ebullition rates in Zostera marina meadows in Virginia, U.S.A. using simple funnel traps and analyzed the oxygen concentration and isotopic composition of the captured gas. Maximum hourly rates of oxygen ebullition (3.0 mmol oxygen m −2 h −1 ) were observed during the coincidence of high irradiance and low tides, particularly in the afternoon when oxygen and temperature maxima occurred. The daily ebullition fluxes (up to 11 mmol oxygen m −2 d −1 ) were roughly equivalent to net primary production rates determined from dissolved oxygen measurements indicating that bubble ebullition can represent a major component of primary production that is not commonly included in ecosystem‐scale estimates. Oxygen content comprised 20–40% of the captured bubble gas volume and correlated negatively with its δ 18 O values, consistent with a predominance of mixing between the higher δ 18 O of atmospheric oxygen in equilibrium with seawater and the lower δ 18 O of oxygen derived from photosynthesis. Thus, future studies interested in the metabolism of highly productive, shallow water ecosystems, and particularly those measuring in situ oxygen flux, should not ignore the bubble formation and ebullition processes described here.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Editorial: Canopies in Aquatic Ecosystems: Integrating Form, Function, and Biophysical Processes - Julia E. Samson; Marco Ghisalberti; Matthew Philip Adams; Matthew A. Reidenbach; Matthew H. Long; Uri Shavit; Virginia B. Pasour (Frontiers in Marine Science, 2019)

Mapping and characterization of two stem rust resistance genes derived from cultivated emmer wheat accession PI 193883 - Jyoti S. Sharma; Qijun Zhang; Matthew N. Rouse; Daryl L. Klindworth; Timothy L. Friesen; Yunming Long; Pablo D. Olivera; Yue Jin; Phillip E. McClean; Steven S. Xu; Justin D. Faris (Theoretical and Applied Genetics, 2019)

Closing the oxygen mass balance in shallow coastal ecosystems - Matthew H. Long; Jennie E. Rheuban; Daniel C. McCorkle; David J. Burdige; Richard C. Zimmerman (Limnology and Oceanography, 2019)
The oxygen concentration in marine ecosystems is influenced by production and consumption in the water column and fluxes across both the atmosphere–water and benthic–water boundaries. Each of these fluxes has the potential to be significant in shallow ecosystems due to high fluxes and low water volumes. This study evaluated the contributions of these three fluxes to the oxygen budget in two contrasting ecosystems, a Zostera marina (eelgrass) meadow in Virginia, U.S.A., and a coral reef in Bermuda. Benthic oxygen fluxes were evaluated by eddy covariance. Water column oxygen production and consumption were measured using an automated water incubation system. Atmosphere–water oxygen fluxes were estimated by parameterizations based on wind speed or turbulent kinetic energy dissipation rates. We observed significant contributions of both benthic fluxes and water column processes to the oxygen mass balance, despite the often‐assumed dominance of the benthic communities. Water column rates accounted for 45% and 58% of the total oxygen rate, and benthic fluxes accounted for 23% and 39% of the total oxygen rate in the shallow (~ 1.5 m) eelgrass meadow and deeper (~ 7.5 m) reef site, respectively. Atmosphere–water fluxes were a minor component at the deeper reef site (3%) but a major component at the shallow eelgrass meadow (32%), driven by diel changes in the sign and strength of atmosphere–water gradient. When summed, the measured benthic, atmosphere–water, and water column rates predicted, with 85–90% confidence, the observed time rate of change of oxygen in the water column and provided an accurate, high temporal resolution closure of the oxygen mass balance.

Perspective: Something Old, Something New? Review of Wasting and Other Mortality in Asteroidea (Echinodermata) - Ian Hewson; Brooke Sullivan; Elliot W. Jackson; Qiang Xu; Hao Long; Chenggang Lin; Eva Marie Quijano Cardé; Justin Seymour; Nachshon Siboni; Matthew R. L. Jones; Mary A. Sewell (Frontiers in Marine Science, 2019)

Dynamic modeling of barrier island response to hurricane storm surge under future sea level rise - Davina L. Passeri; Matthew V. Bilskie; Nathaniel G. Plant; Joseph W. Long; Scott C. Hagen (Climatic Change, 2018)

Benchmark dose analyses of multiple genetic toxicity endpoints permit robust, cross-tissue comparisons of MutaMouse responses to orally delivered benzo[a]pyrene - Alexandra S. Long; John W. Wills; Dorothy Krolak; Matthew Guo; Stephen D. Dertinger; Volker M. Arlt; Paul A. White (Archives of Toxicology, 2018)

Homeostatic plasticity in human extrastriate cortex following a simulated peripheral scotoma - Matthew A. Gannon; Stephanie M. Long; Nathan A. Parks (Experimental Brain Research, 2017)

A novel strategy to enhance angiogenesis in vivo using the small VEGF-binding peptide PR1P - Avner Adini; Irit Adini; Zai-long Chi; Ratmir Derda; Amy E. Birsner; Benjamin D. Matthews; Robert J. D’Amato (Angiogenesis, 2017)

Physical mapping of DNA markers linked to stem rust resistance gene Sr47 in durum wheat - Daryl L. Klindworth; Jyoti Saini; Yunming Long; Matthew N. Rouse; Justin D. Faris; Yue Jin; Steven S. Xu (Theoretical and Applied Genetics, 2017)

Shifting targets: spatial priorities for ex situ plant conservation depend on interactions between current threats, climate change, and uncertainty - Adam B. Smith; Quinn G. Long; Matthew A. Albrecht (Biodiversity and Conservation, 2016)

Potential Species Replacements for Black Ash (Fraxinus nigra) at the Confluence of Two Threats: Emerald Ash Borer and a Changing Climate - Louis Iverson; Kathleen S. Knight; Anantha Prasad; Daniel A. Herms; Stephen Matthews; Matthew Peters; Annemarie Smith; Diane M. Hartzler; Robert Long; John Almendinger (Ecosystems, 2016)

Terrestrial and marine perspectives on modeling organic matter degradation pathways - Adrian B. Burd; Serita Frey; Anna Cabre; Takamitsu Ito; Naomi M. Levine; Christian Lønborg; Matthew Long; Marguerite Mauritz; R. Quinn Thomas; Brandon M. Stephens; Tom Vanwalleghem; Ning Zeng (Global Change Biology, 2016)
Organic matter (OM) plays a major role in both terrestrial and oceanic biogeochemical cycles. The amount of carbon stored in these systems is far greater than that of carbon dioxide (CO 2 ) in the atmosphere, and annual fluxes of CO 2 from these pools to the atmosphere exceed those from fossil fuel combustion. Understanding the processes that determine the fate of detrital material is important for predicting the effects that climate change will have on feedbacks to the global carbon cycle. However, Earth System Models (ESMs) typically utilize very simple formulations of processes affecting the mineralization and storage of detrital OM. Recent changes in our view of the nature of this material and the factors controlling its transformation have yet to find their way into models. In this review, we highlight the current understanding of the role and cycling of detrital OM in terrestrial and marine systems and examine how this pool of material is represented in ESMs. We include a discussion of the different mineralization pathways available as organic matter moves from soils, through inland waters to coastal systems and ultimately into open ocean environments. We argue that there is strong commonality between aspects of OM transformation in both terrestrial and marine systems and that our respective scientific communities would benefit from closer collaboration.

A unifying gravity framework for dispersal - Eelke Jongejans; Olav Skarpaas; Matthew J. Ferrari; Eric S. Long; Joseph T. Dauer; Carrie M. Schwarz; Emily S. J. Rauschert; Randa Jabbour; David A. Mortensen; Scott A. Isard; David A. Lieb; Zeynep Sezen; et al. (Theoretical Ecology, 2015)

Anti-centrosome antibodies in breast cancer are the expression of autoimmunity - Marie-Claire Maroun; Ofelia Olivero; Leonard Lipovich; Azadeh Stark; Larry Tait; Sudeshna Bandyopadhyay; Matthew Burke; Richard Zarbo; Dhananjay Chitale; S. David Nathanson; Mike Long; Carol Peebles; et al. (Immunologic Research, 2014)

Identification and characterization of a carboxysomal γ-carbonic anhydrase from the cyanobacterium Nostoc sp. PCC 7120 - Charlotte de Araujo; Dewan Arefeen; Yohannes Tadesse; Benedict M. Long; G. Dean Price; Roger S. Rowlett; Matthew S. Kimber; George S. Espie (Photosynthesis Research, 2014)

A consensus map for Ug99 stem rust resistance loci in wheat - Long-Xi Yu; Hugues Barbier; Matthew N. Rouse; Sukhwinder Singh; Ravi P. Singh; Sridhar Bhavani; Julio Huerta-Espino; Mark E. Sorrells (Theoretical and Applied Genetics, 2014)

Community context mediates the top‐down vs. bottom‐up effects of grazers on rocky shores - Matthew E. S. Bracken; Renee E. Dolecal; Jeremy D. Long (Ecology, 2014)
Interactions between grazers and autotrophs are complex, including both top‐down consumptive and bottom‐up facilitative effects of grazers. Thus, in addition to consuming autotrophs, herbivores can also enhance autotroph biomass by recycling limiting nutrients, thereby increasing nutrient availability. Here, we evaluated these consumptive and facilitative interactions between snails ( Littorina littorea ) and seaweeds ( Fucus vesiculosus and Ulva lactuca ) on a rocky shore. We partitioned herbivores' total effects on seaweeds into their consumptive and facilitative effects and evaluated how community context (the presence of another seaweed species) modified the effects of Littorina on a focal seaweed species. Ulva , the more palatable species, enhanced the facilitative effects of Littorina on Fucus. Ulva did not modify the consumptive effect of Littorina on Fucus . Taken together, the consumptive and facilitative effects of snails on Fucus in the presence of Ulva balanced each other, resulting in no net effect of Littorina on Fucus . In contrast, the only effect of Fucus on Ulva was to enhance consumptive effects of Littorina on Ulva . Our results highlight the necessity of considering both consumptive and facilitative effects of herbivores on multiple autotroph species in order to gain a mechanistic understanding of grazers' top‐down and bottom‐up roles in structuring communities.

Early Airway Structural Changes in Cystic Fibrosis Pigs as a Determinant of Particle Distribution and Deposition - Maged Awadalla; Shinjiro Miyawaki; Mahmoud H. Abou Alaiwa; Ryan J. Adam; Drake C. Bouzek; Andrew S. Michalski; Matthew K. Fuld; Karen J. Reynolds; Eric A. Hoffman; Ching-Long Lin; David A. Stoltz (Annals of Biomedical Engineering, 2014)

Historical and Future Trends in Ocean Climate and Biogeochemistry - Scott Doney; Laurent Bopp; Matthew Long (Oceanography, 2014)

Quantifying global climate feedbacks, responses and forcing under abrupt and gradual CO2 forcing - David J. Long; Matthew Collins (Climate Dynamics, 2013)

Eddy correlation measurements of oxygen fluxes in permeable sediments exposed to varying current flow and light - Peter Berg; Matthew H. Long; Markus Huettel; Jennie E. Rheuban; Karen J. McGlathery; Robert W. Howarth; Kenneth H. Foreman; Anne E. Giblin; Roxanne Marino (Limnology and Oceanography, 2013)
Based on noninvasive eddy correlation measurements at a marine and a freshwater site, this study documents the control that current flow and light have on sediment‐water oxygen fluxes in permeable sediments. The marine sediment was exposed to tidal‐driven current and light, and the oxygen flux varied from night to day between −29 and 78 mmol m −2 d −1 . A fitting model, assuming a linear increase in oxygen respiration with current flow, and a photosynthesis‐irradiance curve for light‐controlled production reproduced measured fluxes well ( R 2 = 0.992) and revealed a 4‐fold increase in oxygen uptake when current velocity increased from ∼ 0 to 20 cm s −1 . Application of the model to a week‐long measured record of current velocity and light showed that net ecosystem metabolism varied substantially among days, between −27 and 31 mmol m −2 d −1 , due to variations in light and current flow. This variation is likely typical of many shallow‐water systems and highlights the need for long‐term flux integrations to determine system metabolism accurately. At the freshwater river site, the sediment‐water oxygen flux ranged from −360 to 137 mmol m −2 d −1 . A direct comparison during nighttime with concurrent benthic chamber incubations revealed a 4.1 times larger eddy flux than that obtained with chambers. The current velocity during this comparison was 31 cm s −1 , and the large discrepancy was likely caused by poor imitation by the chambers of the natural pore‐water flushing at this high current velocity. These results emphasize the need for more noninvasive oxygen flux measurements in permeable sediments to accurately assess their role in local and global carbon budgets.

Stability Enhancement of Drug Layered Pellets in a Fixed Dose Combination Tablet - Matthew D. Burke; Xiaorong He; Chris Cook; Greg A. Petrov; Susan Long; Mark D. Coffin (AAPS PharmSciTech, 2013)

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

How Human Household Size Affects the Habitat of Black-and-White Snub-Nosed Monkeys (Rhinopithecus bieti) in Hongla Snow Mountain Nature Reserve in Tibet, China - Rui-Chang Quan; Yong Huang; Matthew W. Warren; Qi-Kun Zhao; Guopeng Ren; Sheng Huo; Yongcheng Long; Jianguo Zhu (International Journal of Primatology, 2011)

The formation and evolution of an isolated submarine valley in the North Channel, Irish Sea: an investigation of Beaufort's Dyke - Alexander Callaway; Rory Quinn; Craig J. Brown; Matthew Service; David Long; Sara Benetti (Journal of Quaternary Science, 2011)
Beaufort's Dyke is a submarine depression located in the North Channel of the Irish Sea. With a maximum depth of 312 m, the dyke is one of the deepest areas within the European continental shelf. Integration and interpretation of 450 km of sparker seismic data and full‐coverage bathymetric data derived from multi‐beam echo sounder surveys allow for the investigation of the formation processes of Beaufort's Dyke and the evolution of geomorphological features within it. The dyke, formed by composite subglacial processes dominated by subglacial meltwater discharge, is interpreted as a tunnel valley. The regional isolation of Beaufort's Dyke may be explained by the bounding of the North Channel by the bedrock masses of Ireland and Scotland, coupled with the exploitation of structural weakness along a fault plane and presence of halite in the eroded substrate enhancing the erosive potential of the overlying glacier. Beaufort's Dyke has probably been maintained as an open feature by strong rectilinear tidal currents. The morphology of lunate sediment waves and a large parabolic bedform towards the south of the dyke contradict the observed dominant S–N mean hydrodynamic flow recorded within the North Channel, suggesting an alternative hydrodynamic regime either within the dyke or during bedform creation. Copyright © 2011 John Wiley & Sons, Ltd.

Ice stream influence on West Greenland Ice Sheet dynamics during the Last Glacial Maximum - David H. Roberts; Antony J. Long; Bethan J. Davies; Matthew J. R. Simpson; Christoph Schnabel (Journal of Quaternary Science, 2010)
This paper investigates the processes governing bedrock bedform evolution in ice sheet and ice stream areas in central West Greenland, and explores the evidence for a cross‐shelf ice stream at the Last Glacial Maximum (LGM). To the east of Sisimiut the formation of streamlined bedforms with high elongation ratios and high bedform density has been controlled by geological structure and topography in slow‐flowing ice sheet areas. At the coast, the effects of regional flow convergence, caused by coastal fjord orientation, routed ice into the Sisimiut/Itilleq area where it formed an ice stream onset zone. This funnelled ice into an offshore trough (Holsteinsborg Dyb), resulting in a southwesterly regional ice flow direction and the formation of a topographically routed ice stream (Holsteinsborg Isbrae). To the south of this, striae and bedform evidence show that local valley glaciers initially flowed east to west across the coast, but were later redirected by the Itilleq Fjord ice which turned southwestward due to diffluent flow and deflection by Holsteinsborg Isbrae. Roches moutonnées in this area have low elongation ratios and high bedform density, but do not provide unequivocal support for ice streaming, as they are a product of both bedrock structure and changes in ice flow direction, rather than enhanced flow velocities. Cosmogenic surface exposure ages limit maximum ice sheet surface elevation to ca. 755–810 m above sea level in this region. Such ice thickness enabled Holsteinsborg Isbrae to reach the mid/outer continental shelf during the LGM, and to contribute to the formation of a trough mouth fan and the Outer Hellefisk moraines. Initial deglaciation across this region was driven by rising sea level and increasing air temperatures prior to the Bølling Interstadial at ca. 14.5 cal. ka BP. Between 12 and 10 cal. ka BP both increased air and ocean temperatures post the Younger Dryas, and peak sea‐level rise up to the marine limit, caused accelerated thinning and marginal retreat through calving, although dating evidence suggests ice streams remained along the inner shelf/coast boundary until at least ca. 10 cal. ka BP, their longevity maintained by increased ice thickness and ice discharge. Copyright © 2009 John Wiley & Sons, Ltd.

The role of organic acid exudates in liberating phosphorus from seagrass‐vegetated carbonate sediments - Matthew H. Long; Karen J. McGlathery; Joseph C. Zieman; Peter Berg (Limnology and Oceanography, 2008)
Sediment‐bound phosphorus (P) is a potential nutrient source for P‐limited seagrasses inhabiting carbonate sediments. We explored the role of organic acid (OA) exudation by seagrasses in liberating mineral P from carbonate sediments. Organic acids can act to increase available P by dissolving carbonate sediment, competing with P for binding sites and complexing dissolution end products, and also by fueling microbial processes that change pore‐water pH. We used dialysis tubing placed around individual roots in situ to quantify dissolved species immediately adjacent to roots (root zone) and compared these to bulk pore‐water concentrations in vegetated and nonvegetated sediments. Total OA concentrations were highest in the root zone (29.8 ± 1.8 [mol L −1 ) compared to bulk measures of 15.5 ± 1.9 and 7.5 ± 0.6 [mol L −1 in vegetated and nonvegetated sediments, respectively. Phosphate concentrations were also highest in the root zone and were linearly related to OA concentrations ( R 2 = 0.63). Organic acid concentrations increased along a seagrass productivity gradient, and ratios of OA concentrations to productivity showed a significant response to a gradient in P‐limitation of seagrasses. Organic acid concentrations found in and around roots, compared to those found in bulk sediment measures, indicate that seagrasses are a significant source of OA. Sampling at small spatial scales (mm) immediately adjacent to the roots is critical, because bulk sediment pore‐water measures did not capture the observed fluctuations caused by the rapid reaction and consumption of OA in the sediment. Root‐zone processes can liberate considerable quantities of P, and OA exudates likely contribute significantly to the success of T. testudinum in P‐limited environments.

Future atmospheric CO 2 leads to delayed autumnal senescence - GAIL TAYLOR; MATTHEW J. TALLIS; CHRISTIAN P. GIARDINA; KEVIN E. PERCY; FRANCO MIGLIETTA; POOJA S. GUPTA; BENIAMINO GIOLI; CARLO CALFAPIETRA; BIRGIT GIELEN; MARK E. KUBISKE; GIUSEPPE E. SCARASCIA‐MUGNOZZA; KATRE KETS; et al. (Global Change Biology, 2008)
Growing seasons are getting longer, a phenomenon partially explained by increasing global temperatures. Recent reports suggest that a strong correlation exists between warming and advances in spring phenology but that a weaker correlation is evident between warming and autumnal events implying that other factors may be influencing the timing of autumnal phenology. Using freely rooted, field‐grown Populus in two Free Air CO 2 Enrichment Experiments (AspenFACE and PopFACE), we present evidence from two continents and over 2 years that increasing atmospheric CO 2 acts directly to delay autumnal leaf coloration and leaf fall. In an atmosphere enriched in CO 2 (by ∼45% of the current atmospheric concentration to 550 ppm) the end of season decline in canopy normalized difference vegetation index (NDVI) – a commonly used global index for vegetation greenness – was significantly delayed, indicating a greener autumnal canopy, relative to that in ambient CO 2 . This was supported by a significant delay in the decline of autumnal canopy leaf area index in elevated as compared with ambient CO 2 , and a significantly smaller decline in end of season leaf chlorophyll content. Leaf level photosynthetic activity and carbon uptake in elevated CO 2 during the senescence period was also enhanced compared with ambient CO 2 . The findings reveal a direct effect of rising atmospheric CO 2 , independent of temperature in delaying autumnal senescence for Populus , an important deciduous forest tree with implications for forest productivity and adaptation to a future high CO 2 world.

Isolation basin stratigraphy and Holocene relative sea-level change on Arveprinsen Ejland, Disko Bugt, West Greenland - Antony J. Long; David H. Roberts; Matthew R. Wright (Journal of Quaternary Science, 1999)